mHealth mood monitoring for people with COPD - Whelan, M; Velardo, C; Rutter, H; Tarassenko, L; Farmer, A (European Respiratory Society, 2019)
Background: Co-morbid anxiety and depression can add to the complexity of chronic obstructive pulmonary disease (COPD). While digital health technologies for people with COPD support monitoring of vital signs (including oxygen saturation and pulse), mood is not routinely monitored even though it could support self-management.